2005
DOI: 10.3748/wjg.v11.i30.4661
|View full text |Cite
|
Sign up to set email alerts
|

Expression of MUC1 and its significance in hepatocellular and cholangiocarcinoma tissue

Abstract: Expression and localization of MUC1 proteins in primary liver carcinomas (PLCs) may act as prognostic markers, and MUC1 molecules might be helpful in differential diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 35 publications
3
40
0
Order By: Relevance
“…Tumors with high levels of expression, either massforming or periductal-infiltrating, have a poorer prognosis than intraductal-papillary tumors that display a lower level of MUC1 expression. In another surgical series, metastases 3 years after surgical resection were higher in the MUC1 positive group of patients with intrahepatic cholangiocarcinoma (43).…”
Section: Inflammation and Carcinogenesismentioning
confidence: 99%
“…Tumors with high levels of expression, either massforming or periductal-infiltrating, have a poorer prognosis than intraductal-papillary tumors that display a lower level of MUC1 expression. In another surgical series, metastases 3 years after surgical resection were higher in the MUC1 positive group of patients with intrahepatic cholangiocarcinoma (43).…”
Section: Inflammation and Carcinogenesismentioning
confidence: 99%
“…Of the nine studies that have examined the prognostic value of MUC1 in CC, all except one have demonstrated a significant correlation between MUC1 expression and decreased survival, both on univariate and multivariate survival analyses (61,62,(101)(102)(103)(104)(105)(106)(107).…”
Section: Muc1mentioning
confidence: 99%
“…However, the incidence is higher in other regions of the world with an overall world incidence of 14.2 per 100,000 population in males and 6.0 per 100,000 population in females and a highest incidence of 53.1 and 34.2, respectively, in Mongolia [2]. Hepatocellular carcinoma (HCC) and cholangiocarcinoma are the two main types of primary liver cancer, HCC being more common than cholangiocarcinoma [3,4].…”
mentioning
confidence: 99%